2008
DOI: 10.1016/j.rapm.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hemodynamic Effects of a Single 5 mg/kg Dose of Lidocaine With or Without Epinephrine for Thoracic Paravertebral Block

Abstract: Addition of epinephrine to lidocaine when performing thoracic paravertebral block, attenuates the cardiodepressive effects associated with the systemic absorption of lidocaine and also, as a result of the beta-adrenergic consequences of epinephrine, systemic absorption from the paravertebral space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Other trials also showed a significant decrease in MAP values between 30 and 45 minutes from block administration ( 3 , 30 ). Garutti et al ( 30 ) explained the hypotension as due to the prompt resorption and vasodilating effect of lidocaine and the unrecognized hypovolemic state of the patient. Our trial confirmed the results published by previous studies regarding the hemodynamic changes, namely the increase in SVV, decrease in MAP and CO, and minimal changes in HR ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Other trials also showed a significant decrease in MAP values between 30 and 45 minutes from block administration ( 3 , 30 ). Garutti et al ( 30 ) explained the hypotension as due to the prompt resorption and vasodilating effect of lidocaine and the unrecognized hypovolemic state of the patient. Our trial confirmed the results published by previous studies regarding the hemodynamic changes, namely the increase in SVV, decrease in MAP and CO, and minimal changes in HR ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 82%
“…The reason was that we wanted to be certain that the block was successful before using minimally invasive hemodynamic monitoring. To increase measurement precision, the measurement intervals were set at 5 minutes during the first hour, while in other studies, measurements were set at 15-minute intervals during the first hour ( 3 , 30 ). Other trials also showed a significant decrease in MAP values between 30 and 45 minutes from block administration ( 3 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two small trials (with a total of 20 patients in the PVB groups between them) were published in French. 1 80 One trial 38 investigated specifically the haemodynamics of PVB and reported no data on pain or pulmonary function (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%